Pressures for sub-supplier sustainability compliance: the importance of target markets in textile and garment supply chains - Fontana, Enrico; Atif, Muhammad; Sarwar, Huma (Wiley, 2024)
We propose that sub-supplier sustainability compliance in developing economies' textile and garment supply chains can be more effectively realized by understanding sub-suppliers' target markets. We introduce the concept of sub-suppliers' customer share of production as the share of production that sub-suppliers sell to “exporting” direct suppliers that cater to the international market vis-à-vis “local” direct suppliers that cater to the domestic market. Through this concept and qualitative evidence, we offer a model outlining that as sub-suppliers sell more to exporting direct suppliers, they encounter increased coercive, competitive, and collaborative pressures for sustainability compliance. This article contributes to the multi-tier sustainable supply chain management literature by illustrating how target markets exert pressures for sub-supplier sustainability compliance, and why some sub-suppliers are more inclined to invest in sustainability compliance, some decouple from it, and others invest beyond compliance. We conclude with business strategy guidelines for managers in textile and garment supply chains.
Keywords: business strategy; customer share of production; multi-tier sustainable supply chain management; sub-suppliers; sustainability compliance; target markets